Predictive model of proficiency in powered mobility of children and young adults with motor impairments. (21st May 2019) - Gefen, Naomi; Rigbi, Amihai; Weiss, Patrice L
Abstract : Aim: To identify variables that can predict proficiency in powered mobility use for children in young adults. Method: Participants included 80 children and young adults (42 males, 38 females; mean age 10y 2mo, [SD 5y 1mo]; range: 2–22y) with cerebral palsy, neuromuscular disease, and spinal cord injury who participated in the ALYN Hospital Powered Mobility Lending Program from 2009 to 2016. Data were collected and compared before and after participation in the program and powered mobility levels were determined by the Israeli Ministry of Health (MOH) Powered Mobility Proficiency Test. Multivariate logistic regression analysis followed by a bootstrapping procedure that was based on 1000 samples were used to determine if the variables were predictive of success on the Israeli MOH Powered Mobility Proficiency Test. Results: Significant variables for predicting success were identified: manual wheelchair propulsion, go‐stop voluntarily upon request, and using a joystick. The model was able to correctly identify 80% of the children. Interpretation: Children and young adults with the ability to go‐stop upon request, propel a manual wheelchair short distances, and use a joystick to activate the powered wheelchair had a higher chance of becoming proficient. In countries where wheelchair proficiency is a requirement for powered wheelchair procurement, these findings may support policy changes, as they did in Israel. What this paper adds: Using powered wheelchairs offers children earlier and more natural practice to determine driving proficiency. Manual wheelchair propulsion, go‐stop voluntarily upon request, and using a joystick were predictors of powered mobility proficiency. More than 80% of children use a joystick with their hand to activate a powered wheelchair. What this paper adds: Using powered wheelchairs offers children earlier and more natural practice to determine driving proficiency. Manual wheelchair propulsion, go‐stop voluntarily upon request, and using a joystick were predictors of powered mobility proficiency. More than 80% of children use a joystick with their hand to activate a powered wheelchair. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Video Podcast: https://www.youtube.com/watch?v=H2nWKWx6770&feature=youtu.be Resumen: Modelo predictivo de la competencia en movilidad motorizada de niños y adultos jóvenes con deficiencias motoras: Objetivo: Identificar variables que puedan predecir la capacidad de uso de la movilidad motorizada para niños en adultos jóvenes. Método: Fueron incluidos 80 niños y adultos jóvenes (42 varones, 38 mujeres; edad media 10a 2m, [SD 5a 1m]; rango: 2–22a) con parálisis cerebral, enfermedad neuromuscular y lesión de la médula espinal que participaron en el Programa de Movilidad Motorizada del ALYN Hospital del 2009 a 2016. Los datos se recopilaron y compararon antes y después de la participación en el programa y los niveles de movilidad impulsados ​​se determinaron mediante la Prueba de competencia de movilidad impulsada por el Ministerio de Salud de Israel. Se utilizó el análisis de regresión logística multivariable seguido de un procedimiento de arranque que se basó en 1000 muestras para determinar si las variables eran predictivas de éxito en la Prueba de Competencia de Movilidad Movida por MOH de Israel. Resultados: Se identificaron variables significativas para predecir el éxito: propulsión manual en silla de ruedas, posibilidad de arranque y freno a la orden, y uso de un joystick. El modelo fue capaz de identificar correctamente al 80% de los niños. Interpretación: Los niños y adultos jóvenes que tienen la capacidad de detenerse cuando se lo requiere, que pueden impulsar una silla de ruedas manual a corta distancia y que pueden usar un joystick para activar la silla de ruedas motorizada tienen una mayor probabilidad de convertirse en expertos. En los países donde el dominio de las sillas de ruedas es un requisito para la adquisición de sillas de ruedas motorizadas, estos hallazgos pueden respaldar cambios en las políticas, como lo hicieron en Israel. Resumo: Modelo preditivo de proficiência na mobilidade motorizada de crianças e adultos com deficiências motoras: Objetivo: Identificar variáveis que podem predizer proficiência no uso da mobilidade motorizada para crianças e adultos jovens. Método: Os participantes incluíram 80 crianças e jovens adultos (42 do sexo masculino, 38 do sexo feminino; média de idade 10a 2m, [DP 5a 1m]; variação: 2–22a) com paralisia cerebral, doença neuromuscular, e lesão da medula espinhal que participaram do Programa de Mobilidade Motorizada do Hospital ALYN de 2009 a 2016. Os dados foram coletados e comparados antes e após a participação no programa, e os níveis de mobilidade motorizada foram determinados pelo Teste de Proficiência em Mobilidade Motorizada do Ministério da Saúde (MS) Israelense. Análise de regressão logística multivariada seguida por procedimento e bootstrapping baseado em 1.000 amostras foi usada para determiner se as variáveis eram preditivas do sucesso no Teste de Proficiência em Mobilidade Motorizada do MS Israelense. Resultados: Variáveis significativas na predição de sucesso foram identificadas: propulsão da cadeira manual, capacidade de iniciar e parar voluntariamente quando solicitado, e uso de controle do tipo joystick. O modelo foi capaz de identificar corretamente 80% das crianças. Interpretação: Crianças e adultos jovens com a capacidade de iniciar e parar quando solicitados, de impulsionar uma cadeira de rodas manual por distâncias curtas, e usar um joystick para ativar a cadeira de rodas tiveram maior chance de se tornar proficientes. Em países em que a proficiência na cadeira é um requisite para solicitar a cadeira de rodas motorizada, estes achados podem dar suporte a mudanças nas políticas empregadas, como ocorreu em Israel.